MENGUKUR KINERJA PERUSAHAAN MENGGUNAKAN ANALISA RASIO LAPORAN KEUANGAN DENGAN MS. EXCEL - Suhartono, Suhartono (www.bsi.ac.id, 2009)
In facing emulation of business, every company need to have ability of good management to be able tostand at bay continuing its(the business). One thing important that need to be paid attention by company isfinancial statement ratio analysis. Good financial statement ratio analysis has a real big influence to decisionmaking processes good for the side of intern and also ekstern company so that will assist existence and progress of a company. Analisis' process financial statement ratio will increase meteoric and results accurate data and up to date if utilize computer software on of it by use of Ms. Excel.Key Words: Measuring the performance of the company, Financial Statement Analysis,MS.Excel